Pertanggungjawaban Pidana Guru atas Tindak Kekerasan terhadap Siswa Perspektif Peraturan Perundang-undangan di Indonesia - Afrizal, Afrizal; Lasmadi, Sahuri; Siregar, Elizabeth (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Education is a fundamental right of every citizen, with teachers playing a central role in the learning process and in shaping students' character. However, the increasing incidence of violence in schools and criminal reports filed against teachers while enforcing discipline have created significant legal issues. This study aims to examine the regulation of teachers’ criminal liability for acts of violence against students and to formulate a more ideal regulatory model for the future. The research employs a normative juridical method by analyzing statutory regulations and relevant legal concepts. The results indicate that regulations prohibiting violence against children are clearly established; however, they are not fully harmonized with regulations granting teachers the authority to discipline students. Consequently, teachers are often subjected to criminal proceedings without adequate consideration of the educational context and the element of culpability. This situation has reduced teachers’ ability and confidence to educate and shape students’ character effectively. The study concludes that a regulatory framework is needed that places criminal law as a measure of last resort (ultimum remedium), prioritizing resolution through ethical and administrative mechanisms before criminal sanctions are imposed. Such an approach would create a balance between protecting students and safeguarding the teaching profession.